Management of emotion in computermediated communication (CMC) - Peña Acuña, Beatriz; Rubio Vega, Mónica (Estudios sobre el Mensaje Periodístico, 2013)
Concordance exists among some researchers who argue that the emotional communication occurs both in the face and in ComputerMediated Communication (CMC), in the same way that they agree that this communication occurs with different characteristics in both situations. Studies examining these differences in the Spanish research environment are few and very recent, but already suggest a series of singularities. In this study, we analyze the expression of emotions in CMC from a survey of digital native university students that produce their naturally emotional communication both in person and through computer.